Photoactive Ni-Complexes in Metallaphotoredox Catalysis: A Successful Match in C–C Cross-Coupling Reactions - Dang, Luzhen; Zhu, Chuan; Feng, Chao (Synthesis, 2024)
Nickel catalysis is a well-established and powerful tool for C–C cross-coupling reactions, and its versatility has expanded significantly over past decades by its combination with visible-light photocatalysis in metallaphotoredox chemistry. Photocatalysis enables the activation of traditionally inert substrates and turnover of the Ni catalyst through a single-electron transfer processes. In recent years, dual catalysis has been further empowered by photoactive Ni intermediates, which exhibit distinct reactivity profiles from their ground states and complement existing protocols. This short review focuses on the emergent subclass of metallaphotoredox catalysis in which the synergy of a photoactive Ni catalyst and a typical photocatalyst (e.g., a polypyridyl Ir complex) provide solutions to challenging C–C bond formation.1 Introduction2 Photoactive Nickel Complexes3 HAT-Mediated C–C Cross-Coupling4 Halofunctionalization of π-Systems5 Photoelimination of an Aryl Radical6 Conclusion
Keywords: Ni/photoredox catalysis; photoactive nickel complex; synergistic catalysis; halogen radical; hydrogen atom transfer